Experimental Measurement and Numerical Modeling of the Creaming of mPCM Slurry. (November 2015) - Fan, Xueliang; Serale, Gianluca; Capozzoli, Alfonso; Perino, Marco
Abstract: The slurry of mPCM has been widely used for enhancing heat transfer and reducing building energy consumption. Because of intrinsic density differences between mPCM and water, the slurry is subject to creaming phenomena. As a consequence the viscosity of slurry increases and the thermal properties decrease. Up to now no quantitative analysis about the creaming of mPCM has been done. In the paper experimental measurement and numerical modeling of the creaming of mPCM slurry is presented. Using the optical method, the temporal-spatial distribution of volume concentration is recorded. Based on the conservation model, the process of creaming has been simulated.